PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) DI SEKOLAH DASAR - Hanafi, Rizki (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research of background that study of IPS in Class IV SDN 05 Pasar Baru Kecamatan Bayang Kabupaten Pesisir Selatan, teacher still predominate study process and not yet entangled student participation. The condition result to lower result of learning student. Therefore done conducted by research with aim to to increase result of learning IPS by using Type Problem Based Learning. This Research use Approach qualitative and is quantitative, while research type that is Research of Action Class PTK with research device cover, (1) planning, (2) execution, (3) perception, and (4) refleksi. This Research data in the form of information about result of perception to planning, execution, and result learn student. Result of research be a grow up result of RPP, execution, and result learn student. Become can be concluded that study of IPS by using Type Problem Based Learning can improve result learn IV SDN class student 05 Pasar Baru Kecamatan Bayang Kabupaten Pesisir Selatan.  Kata Kunci: Hasil Belajar Siswa, Pembelajaran IPS, Model Problem Based Learning (PBL).